THE DESIGN OF 4-LEVEL IMPELLER ON CENTRIFUGAL COMPRESSOR ASSISTED CF TURBO SOFTWARE - Budianto, Ricky Gunawan; Sufiyanto, Sufiyanto; Widada, Boe Tong (TRANSMISI, 2019)
Compressor is a compressing device or compressing air in other words a compressor is a compressed air generator. Because of the compression process, air has a higher pressure compared to environmental air pressure (1 atm). In this Final Project the compressor is planned with an output pressure of 140 bar, a flow rate of 5000 m3 / hr, 4 levels, a shaft rotation of 15000 rpm. In the compressor planning, TURBO 10 CF software is used. Input from the software is the flow rate and pressure of each level. As output is the impeller diameter, the output pressure of each impeller. Power of each level. The average impeller diameter is 596 mm. The air coming out of each level is cooled. The cooling system is not planned in the final project.